FAAH, but not MAGL, inhibition modulates acute TLR3‐induced neuroimmune signaling in the rat, independent of sex. Issue 6 (20th July 2017) - Flannery, Lisa E.; Henry, Rebecca J.; Kerr, Daniel M.; Finn, David P.; Roche, Michelle
Abstract: Toll‐like receptor (TLR)3 is a key component of the innate immune response to viral infection. The present study firstly examined whether sex differences exist in TLR3‐induced inflammatory, endocrine, and sickness responses. The data revealed that TLR3‐induced expression of interferon‐ or NFkB‐inducible genes (IFN‐α/β, IP‐10, or TNF‐α), either peripherally (spleen) or centrally (hypothalamus), did not differ between male and female rats, with the exception of TLR3‐induced IFN‐α expression in the spleen of female, but not male, rats 8 hr post TLR3 activation. Furthermore, TLR3 activation increased plasma corticosterone levels, induced fever, and reduced locomotor activity and body weight — effects independent of sex. Thus, the acute‐phase inflammatory, endocrine, and sickness responses to TLR3 activation exhibit minimal sex‐related differences. A further aim of this study was to examine whether enhancing endocannabinoid tone — namely, 2‐arachidonylglycerol (2‐AG) or N ‐arachidonoylethanolamine (AEA), exhibited similar effects on TLR3‐induced inflammatory responses in male versus female rats. Systemic administration of the monoacylglycerol lipase (MAGL) inhibitor MJN110 and subsequent increases in 2‐AG levels did not alter the TLR3‐induced increase in IP‐10, IRF7, or TNF‐α expression in the spleen or the hypothalamus of male or female rats. In contrast, the fatty acid amide hydrolase (FAAH) inhibitor URB597 increased levels of AEA and related N ‐acylethanolamines, an effect associated with the attenuation of TLR3‐induced inflammatory responses in the hypothalamus, but not the spleen, of male and female rats. These data support a role for FAAH, but not MAGL, substrates in the modulation of TLR3‐induced neuroinflammatory responses, effects independent of sex. Abstract : Systemic administration of the viral mimetic poly I:C induces activation of TLR3 and increases the expression of interferon (IFN)‐ and NFκB‐related genes in the periphery and in the brain (hypothalamus). The inhibition of MAGL, and enhanced endogenous levels of 2‐AG, does not alter the expression of TLR3‐induced expression of inflammatory genes in the spleen or hypothalamus of male or female rats. In comparison, administration of the FAAH inhibitor URB597, and subsequent increases in AEA, OEA, and PEA levels, attenuates the TLR3‐induced neuroinflammatory response in the hypothalamus, but not the spleen, of both male and female rats. These data support a role for FAAH, but not MAGL, substrates in the modulation of TLR3‐induced neuroinflammatory responses, effects independent of sex.